REACTIVITY OF ORGANIC MATTER IN AQUIFER SEDIMENTS: GEOLOGICAL AND GEOCHEMICAL CONTROLS - Hartog N.; van Bergen P.F.; de Leeuw J.W.; Griffioen J. (My University, 2004)
Reduction rates in aquifers are commonly carbon limited, but little is known about the molecular composition and degradability of sedimentary organic matter (SOM) in aquifer sediments. The composition, source and degradation status of SOM in aquifer sediments of fluvio-glacial (Pleistocene) and shallow marine (Pliocene) origin, were determined using flash pyrolysis-gas chromatography/mass spectrometry. Incubation experiments (106 d) were used to assess the reactivity of SOM towards molecular oxygen. A dominance of lignin-derived components and long chain odd-over-even predominant alkanes indicate that terrestrial higher land plants were the main source of SOM even in the shallow marine sediments, while bacterial lipid-derived hopanoids and iso- and anteiso-C15 and C17 fatty acids indicate a minor contribution of microbial biomass. No compositional difference was observed between SOM present in the fine (<63 μm) and coarse fraction (63–2000 μm). A significant part of SOM was not present as low-molecular-weight compounds but was macromolecularly bound. For the fluvio-glacial sediments, a relatively higher abundance of resistant macromolecular compounds was in agreement with stronger signs of aerobic lignin, alkane and hopanoid oxidation. The more degraded status of SOM in the fluvio-glacial sediments was consistent with their significantly lower SOM mineralization (2–6%) during incubation, as compared with the shallow marine sediments (9–14%). The reactivity towards oxygen of SOM was controlled by the extent of past aerobic oxidation. Not the age of SOM, but the extent of oxygen exposure during syn- and postdepositional conditions seems most important in affecting the degradation status of SOM in aquifer sediments and thus their ability to reduce oxidants.
Keywords: Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен